The Use of Zoom for Emergency Remote Teaching - De Los Heros Rondenil, Martín Gabriel (Emerging Trends in Education, 2022)
It is a book that helps us to know in a practical and concrete way the use of the Zoom platform, includes pedagogical and technical tips and a checklist for Emergency Remote Education (ERE), which is not only designed for online education in the current circumstances, but also for the post-pandemic stage. The technical and pedagogical tips on the key tools of this platform are addressed to both teachers and students so that they can participate in synchronous (live) or asynchronous activities, so that the teaching-learning process is effective.